2021
DOI: 10.1002/hast.1264
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimer's and Aducanumab: Unjust Profits and False Hopes

Abstract: Accelerated approval of aducanumab for mild Alzheimer's by the U.S. Food and Drug Administration on June 7, 2021, has generated substantial medical, scientific, and ethical controversy. That approval was contrary to the nearly unanimous judgment of the FDA's Advisory Committee that little reliable evidence existed of significant benefit, even though the drug did reduce β‐amyloid. Three major ethical problems were created by this approval: (1) Medicare resources would be unjustly squandered, given the drug's $5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 3 publications
(2 reference statements)
1
10
0
1
Order By: Relevance
“…For the last three decades, over 900 billion USD has been invested in drug development and clinical trials with no proven effective benefit for treating patients with AD [ 56 ]. Multiple studies have recently demonstrated a strong relationship between the pathogenesis of AD and some vascular-associated diseases, including atherosclerosis and hypertension [ 57 , 58 ]. Moreover, Aguilar et al, 2021, have shown that vascular smooth muscle cells contribute to the neuroinflammation and tau hyperphosphorylation in the early and late stages of the disease [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…For the last three decades, over 900 billion USD has been invested in drug development and clinical trials with no proven effective benefit for treating patients with AD [ 56 ]. Multiple studies have recently demonstrated a strong relationship between the pathogenesis of AD and some vascular-associated diseases, including atherosclerosis and hypertension [ 57 , 58 ]. Moreover, Aguilar et al, 2021, have shown that vascular smooth muscle cells contribute to the neuroinflammation and tau hyperphosphorylation in the early and late stages of the disease [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…From June 2021, aducanumab was approved to treat mild AD until today, which has been caused considerable medical and scientific controversy ( Tampi et al, 2021 ). Although aducanumab does reduce Aβ, there is a lack of reliable evidence that it has significant benefits to patients with AD ( Fleck, 2021 ). In phase III, among patients treated with high-dose aducanumab, ∼35% of patients occurred ARIA-related cerebral edema (ARIA-E), and ∼18–22.7% of patients had ARIA-related microhemorrhages (ARIA-H) or other side effects, such as headache, dizziness, and nausea.…”
Section: Immunotherapies With Mabs In Patients With Ad and Its Animal...mentioning
confidence: 99%
“…The FDA should have required a third phase 3 trial with a high-dose of aducanumab before approval. 37 , 59 Secondly, there is no evidence that Aβ reduction correlates with clinical benefits, so the majority of experts consider that Aβ plaques are not a valid surrogate endpoint. 10 , 60 Moreover, recent studies showed that tau accumulation correlates better with cognitive impairment than Aβ.…”
Section: Controversymentioning
confidence: 99%